Development of a highly sensitive immunohistochemical method to detect neurochemical molecules in formalin-fixed and paraffin-embedded tissues from autopsied human brains - Goto, Satoshi; Morigaki, Ryoma; Okita, Shinya; Nagahiro, Shinji; Kaji, Ryuji (Frontiers in Neuroanatomy, 2015)
Immunohistochemistry (IHC) is a valuable method for identifying discrete neurochemical molecules by the interaction of target antigens with validated antibodies tagged with a visible label (e.g., peroxidase). We have developed an immunostaining method that is highly sensitive in detection of neurochemical antigens. Our IHC method involves a hybrid protocol that implements aspects of both the polymer and avidin-biotin-complex (ABC) methods in combination with biotin-tyramide amplification. When using [Met]-enkephalin as a target antigen, the sensitivity of the PBTA method for IHC was more than 100-fold higher compared with the polymer and ABC methods. In addition, its sensitivity for enzyme-linked immunosorbent assay was about 1,000-fold higher compared with the ABC method. We examined the utility of our IHC method for both chromogenic and fluorescence detection systems used to visualize neurochemical peptides and proteins in formalin-fixed, paraffin-embedded tissues from autopsied human brains. The results convincingly demonstrate that under optimal conditions, our IHC method is highly sensitive without increasing non-specific background activities. Our IHC method could be a powerful tool for detection and visualization of neurochemical antigens that are present even in trace amounts in autopsied human brains.